THE POWER OF MYTH NYANGGAR JANUR KUNING AT PENGGING BOYOLALI CENTRAL JAVA - Dewi Puspita Sari; Dwi Susanto; Marimin Marimin (Proceeding of International Conference on Art, Language, and Culture, 2019)
Javanese people is closely related to the myth which origin can be traced back to their ancestors. Mythology, somehow, can be used as a system of oral communication which developed overtime in the societies. A site of religious pilgrim in Pengging, Boyolali, Indonesia, or popularly called ‘the sanctuary of Yosodipuro I, has been a real evidence of the existence of mythology in Javanese people in the modern age. This holy place attracts many people from many regions because its origin story and its formerly religious figure, Yosodipuro I. The visitors believe that by doing religious pilgrim there, can make their dreams come true. The myth tells how Yosodipuro I, a religious figure, is regarded as a mediator of God to the citizens. The existence of mythology in this modern age, somehow, can be caused by the mindsets of the people. These mindsets have constructed code of signs which come within the self. Using the discourse analysis, this paper tells the motive of the visitors in ‘the sanctuary of Yosodipuro I’ by examining the ritual process of Nyanggar Janur Kuning, a fortune – telling. The paper also used Hyper- semiotic to reveal these phenomenon to know that a thing can have many signs. The sign finally reproduces new signs with the unlimited meaning.  The results of the study indicates that people used myth to pursue their dream. Moreover, the visitors change the used-value of this place into the exchange value which represents aspirations.